Rally Post-Terrorism - Shuai Chen (Global Labor Organization (GLO), 2022)
This study examines whether the rally 'round the flag phenomenon is present in the context of terrorist attacks, and investigates the explanations for the related increase of confidence in political institutions and political approval of the incumbent's job performance. I exploit variations in terrorist occurrences and results across sub-national regions among EU countries from 2008 to 2016. I restrict the sample to only regions where at least one attack took place during the data period, in order to mitigate concerns over selectivity of terrorism in particular areas. I empirically show that both terrorism occurrence and its results (successful or failed attacks) are plausibly exogenous to the prior political and economic climate. Conducting a difference-in-differences analysis, I compare changes in political confidence and approval among individuals who were exposed to an attack in their region to those who were not. With another more sophisticated identification, I also compare such political changes after successful attacks to those after failed attacks of the same type. I find that post-terrorism, individual political confidence and support significantly increased by more than 10 percentage points, and that this political increment was 5 percentage points after successful attacks relative to failed ones. Furthermore, I explore various potential channels suggesting patriotism and civic engagement as mechanisms while rejecting perceived economic capture and political acquisition as alternative explanations. This paper first empirically analyzes the driver of the rally effect of terrorism by disentangling voluntary solidarity from economically or politically elicited solidarity.
Keywords: D74; H12; P16; 330; Rally 'round the flag effect; Terrorism; Confidence in institutions; Political approval; Patriotism; Economic capture; Political acquisition